Innovative methods for automated assembly and fixation of permanent magnets in electrical machines - Franke, Jörg; Hofmann, Benjamin; Tremel, Jan; Meyer, Alexander Wilhelm (Procedia CIRP, 2015)
Over the years, the production of electric machines has spread into different designs, creating complex variations in topologies and structure. Based upon a recently completed research project, the handling, assembly and fixation of permanent magnet components for electrical machines containing internal permanent magnets (IPM) is investigated. An assembly and fixation process is presented both of which are economical in terms of use of adhesives and variant flexibility. The developed solution is based on a SCARA-Robot with an attached device that is capable of both separating and assembling the permanent magnet material. The elimination of an off-site magnet separation and a continuous feed of magnets significantly reduces the cycle time for a single rotor. The flexibility of the SCARA concept ensures its application in a broad field of different rotor sizes. Recent solutions for affixing the IPM material are often based on a complete submersion of magnets into resin material. An alternative approach for adhesive application has been developed and integrated into the assembly process that reduces the overall need for adhesive material by over 80%.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Assembly; Fixation; Handling